Increased healthcare service utilizations for patients with dementia: a population-based study. - Shiu-Dong Chung (Public Library of Science (PLoS), 2014)
Background The majority of previous studies investigating the health care utilization of people with dementia were conducted in Western societies. There is little information on the economic burden on the healthcare system attributable to dementia in Asian countries. This study thus investigated differences in utilization of healthcare services between subjects with and those without a diagnosis of dementia using Taiwan's National Health Insurance population-based database. Methods This study comprised 5,666 subjects with a dementia diagnosis and 5,666 age- and gender-matched comparison subjects without a dementia diagnosis. We individually followed each subject for a 1-year period starting from their index date to evaluate their healthcare resource utilization. Healthcare resource utilization included the number of outpatient visits and inpatient days, and the mean costs of outpatient and inpatient treatments. In addition, we divided healthcare resource utilization into psychiatric and non-psychiatric services. Results As for utilization of psychiatric services, subjects with a dementia diagnosis had significantly more outpatient visits (2.2 vs. 0.3, p<0.001) and significantly higher outpatient costs (US$124 vs. US$16, p<0.001) than comparison subjects. For non-psychiatric services, subjects with a dementia diagnosis also had significantly more outpatient visits (34.4 vs. 31.6, p<0.001) and significantly higher outpatient costs (US$1754 vs. US$1322, p<0.001) than comparison subjects. For all healthcare services, subjects with a dementia diagnosis had significantly more outpatient visits (36.7 vs. 32.0, p<0.001) and significantly higher outpatient costs (US$1878 vs. US$1338, p<0.001) than comparison subjects. Furthermore, the total cost was about 2-fold greater for subjects with a dementia diagnosis than for comparison subjects (US$3997 vs. US$2409, p<0.001). Conclusions We concluded that subjects who had received a clinical dementia diagnosis had significantly higher utilization of all healthcare services than comparison subjects.